`-32 - (x - 5) = 0`
`=> x - 5 = -32`
`=> x = -32 + 5`
`=> x = -27`
Vậy ...
``
`-12 + (x - 9) = 0`
`=> x - 9 = 12`
`=> x = 12 + 9`
`=> x = 21`
Vậy ...
``
`11 + (15 - x) = 1`
`=> 15 - x = 1 - 11`
`=> 15 - x = -10`
`=> x = 15 - (-10)`
`=> x = 25`
Vậy ...
a)-32-(x-5)=0
<=>-32-x+5=0
<=>x=-27
vậy nghiệm của pt là x=-27
b)tương tự
c)11+(15-x)=1
<=>11+15-x=1
<=>x=25
vậy nghiệm của pt là x=25
a)-32-(x-5)=-32-0
x-5=-32
x=-32+5
x=-27
Vậy x =-27
c)11+(15-x)=1
15-x=1-15
15-x=-14
x=15-(-14)
x=29
Vậy x=29
b)-12+(x-9)=0
x-9=0-(-12)
x-9=12
x=12+9
x=21
Vậy x=21